Análisis de las motivaciones para certificar la marca "Q de calidad turística": Sector de alojamiento - José Álvarez García; José Antonio Fraiz Brea; María de la Cruz Del Río Rama (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2012)
This paper presents the results of the empirical study conducted in 186 tourist accommodation businesses nationally certified under the Q for Tourist Quality”, presented in order to analyze the motivations that lead companies in the tourism sector implementing and certifying Quality Management Systems. Once a comprehensive theoretical review, the methodology consists of a descriptive analysis and factor analysis in order to determine the structure of these motivations in this sector. Finally, cluster firms and these groups are analyzed to establish their profile by cluster analysis. The results show that the most important motivations that drive hosting companies to implement a system of quality management are internal motivations, this study showing differences with the findings in other academic studies in industrial companies. The structure of motivation in this sector is made up of three groups: external market reasons, external demands reasons and internal reasons.
Keywords: M1; 330; quality management; Q for quality; motivation; factorial and cluster analysis